Association of age and night flight duration with sleep disorders among Chinese airline pilots - Ruizi Shi; Fang Wang; Wanying Xu; Li Fu (Frontiers Media S.A., 2023)
ObjectiveNight flights might aggravate sleep disorders among aging airline pilots, posing a threat to flight safety. In this study, we assess the prevalence of sleep disorders as well as the combined effects of night flight duration and aging on sleep disorders.MethodA cross-sectional study was conducted between July and December, 2021. Participants were recruited from a commercial airline. Sleep disorders were evaluated using the Pittsburgh Sleep Quality Index (PSQI). The interaction effect of night flight duration and age on sleep disorders and their correlates were examined using logistic regression models.ResultsIn total, 1,208 male airline pilots were included in the study, with a median age of 34 (interquartile range [IQR]: 29-39) years. The overall prevalence of sleep disorders was 42.6%. The multivariate logistic regression identified an interaction between night flight duration and age on sleep disorders (adjusted odds ratio [aOR] of the interaction term was 5.85 95% CI: 2.23-15.34 for age ≥ 45 years; 1.96 95% CI:1.01-3.81 for the age group 30-44 years). Longer night flight duration (aOR: 4.55; 95%CI: 1.82-11.38) and body mass index (BMI) ≥28.0 kg/m2 (aOR: 0.16; 95% CI: 0.03-0.91) were significantly associated with sleep disorders in participants aged ≥45 years. Hyperuricemia (aOR: 1.54; 95% CI: 1.09-2.16) and regular exercise (aOR: 0.23; 95% CI: 0.08-0.70) were significantly associated with sleep disorders in the 30-44 years age group.ConclusionThe mean monthly night flight duration and aging had a synergistic effect on airline pilots' sleep disorders, implying an aging and work-related mechanistic pathogenesis of sleep disorders in airline pilots that requires additional exploration and intervention.